The deglaciation of the western sector of the Irish Ice Sheet from the inner continental shelf to its terrestrial margin. (1st June 2020) - Roberts, David H.; Ó Cofaigh, Colm; Ballantyne, Colin K.; Burke, Matthew; Chiverrell, Richard C.; Evans, David J. A.; Clark, Chris D.; Duller, Geoff A. T.; Ely, Jeremy; Fabel, Derek; Small, David; Smedley, Rachel K.; et al.
Abstract : This paper provides a new deglacial chronology for retreat of the Irish Ice Sheet from the continental shelf of western Ireland to the adjoining coastline, a region where the timing and drivers of ice recession have never been fully constrained. Previous work suggests maximum ice‐sheet extent on the outer western continental shelf occurred at 26–24 cal. ka BP with the initial retreat of the ice marked by the production of grounding‐zone wedges between 23–21.1 cal. ka BP. However, the timing and rate of ice‐sheet retreat from the inner continental shelf to the present coast are largely unknown. This paper reports 31 new terrestrial cosmogenic nuclide (TCN) ages from erratics and ice‐moulded bedrock and three new optically stimulated luminescence (OSL) ages on deglacial outwash. The TCN data constrain deglaciation of the near coast (Aran Islands) to 19.5–18.5 ka. This infers ice retreated rapidly from the mid‐shelf after 21 ka, but the combined effects of bathymetric shallowing and pinning acted to stabilize the ice at the Aran Islands. However, marginal stability was short‐lived, with multiple coastal sites along the Connemara/Galway coasts demonstrating ice recession under terrestrial conditions by 18.2–17. ka. This pattern of retreat continued as ice retreated eastward through inner Galway Bay by 16.5 ka. South of Galway, the Kilkee–Kilrush Moraine Complex and Scattery Island moraines point to late stage re‐advances of the ice sheet into southern County Clare 14.1–13.3 ka, but the large errors associated with the OSL ages make correlation with other regional re‐advances difficult. It seems more likely that these moraines are the product of regional ice lobes adjusting to internal ice‐sheet dynamics during deglaciation in the time window 17–16 ka.